Reconstruction of Cloacal Defect: Switch Operation - A New Approach - Ashoke Kumar Basu; Kalyani Saha Basu; Kuntal Bhaumik; Jyotsna Basu; Abhishek Aanad (Wolters Kluwer Medknow Publications, 2024)
Introduction: Reconstruction of a cloacal defect in a girl is often difficult and complicated.[1] This is most often done either by the sacro-perineal route or through the posterior sagittal route.[2] The procedures may involve total mobilization of the cloaca with or without the creation of a lower vagina with the help of a loop of vascularized bowel.[3] In our approach, such defects can be corrected using the lower anorectum for the creation of a lower vagina and abdominoperineal pull-through of the proximal divided bowel. This method can be used both in short and long common channel cloaca. Materials and Methods: We have used this procedure in one patient of posterior cloaca and four patients of anterior cloaca. These operations were done in patients of 1 year and 6 months to 4 years. Only one patient is waiting for the closure of the colostomy. Results: In all the cases, the urethra, the vagina, and the anus were successfully separated. Conclusion: This operation restores normal pelvic anatomy and physiology with minimal mutilation of the pelvic floor.